PENGEMBANGAN PROFESIONAL GURU DALAM PENERAPAN MODEL PENELITIAN TINDAKAN KELAS PADA SMK RUMPUN TEKNOLOGI DI KOTA SEMARANG - Supraptono, Eko; Widodo, Djoko Adi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M), Universitas Negeri Semarang, 2010)
The aim of this research are for descipting many correlation of variebl which can be contributed to policy of the head master or regional leader of educatonal departemen, to explore the resistence of teacher while they implemented the action research project in the class, to expand the moodel of statistic that can contructed. The population in this research are the teacher in study program of vocational in SMKN Teknologi at Semarang City, there are 240 personals. The sample are the teacher in adaptive program, there are 140 personals. With mehod of purposive random sampling, can be took 60 personals. He data analysis by SPSS program. The research finding explained that correlation between leadership and culture organitation 0,86; the corelation of leadership and motivation for reasearh 0,87; the corelation between leadership and motivation for research to implementation of CAR is 0.89; the corelation between supervision and motivation for research to implementation of CAR is 0.77; The resarcherÃ¢â¬Å¸s sugestion is that leadership and culture organitation is must be strong built for supporting the increasing of teacher competency in research, the supervisor program must be a strong direction and best planning. The motivation for research can be improved by the best leadership and supervision give away for implementation of CAR strategy. Keywords: Profesional teacher, CAR, Vocational School